Ethics of the teaching profession as an ethics of care - Dariusz Zając (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
Teachers are among many educational entities. In this profession, it is worth paying special attention to its ethical dimension. This is dictated primarily by the specific nature of the educational activity of the representatives of this socio-professional category which includes, among others, interpersonal relationships with pupils and students. They are manifested in various educational situations, often complex and complicated, requiring the teacher to represent a high ethical level, consistent with the arrangements made in the field of professional ethics. This, in turn, taking into account its shape, may be perceived differently. The aim of this article is to attempt to present the ethics of the teaching profession from the point of view of the ethics of care. Understanding the ethics of the teaching profession as an ethics of care is rarely presented in the literature on the subject. Most often, teaching ethics is associated with a set of specific ethical conditions or moral virtues, somewhat reducing the importance of the category of care in this ethics. Hence, the main research problem revolves around the questions: What are the characteristics of the ethical dimension of a teacher's professional work and what does care and ethics of care mean in the teaching profession? The adopted research method was the analysis of the literature on the subject and of articles published in scientific journals, concerning the research issues being undertaken. The presented text discusses the ethical dimension of a teacher's professional work from a normative perspective, in particular from the point of view of the ethics of duty and the ethics of virtue, and then the category of care and the ethics of care with its relation to the teacher's professional activity. The analysis of the literature on the subject leads to the belief that in contemporary scientific explorations consistent with ethical and pedeutological thought, greater emphasis should be placed on the ethics of care in the teaching profession, as well as the possibility of contamination of the ethics of care and the ethics of justice. All this can serve to optimally practice the teaching profession in ethical terms. Etyka zawodu nauczyciela jako etyka troski Wśród wielu podmiotów edukacji wymienia się nauczyciela. W zawodzie uprawianym przez niego warto zwrócić szczególną uwagę na wymiar etyczny. Podyktowane jest to przede wszystkim specyficznym charakterem aktywności edukacyjnej przedstawicieli tej kategorii społeczno-zawodowej, w którą wpisane są między innymi relacje interpersonalne z uczniami-wychowankami. Manifestują się one w różnorodnych sytuacjach edukacyjnych, niejednokrotnie złożonych i skomplikowanych, wymagających od nauczyciela reprezentowania wysokiego poziomu etycznego, zgodnego z ustaleniami poczynionymi na gruncie etyki zawodowej. Ta z kolei, biorąc pod uwagę jej kształt, może być różnie postrzegana. Celem podejmowanych w niniejszym artykule rozważań jest próba ukazania etyki zawodu nauczyciela z punktu widzenia etyki troski. Ujmowanie etyki zawodu nauczyciela jako etyki troski rzadko eksponowane jest na gruncie literatury przedmiotu. Najczęściej etykę nauczycielską kojarzy się z zespołem określonych obwarowań etycznych bądź cnót moralnych, umniejszając nieco rangi kategorii troski w tej etyce. Stąd też główny problem badawczy oscyluje wokół pytań: Czym charakteryzuje się wymiar etyczny pracy zawodowej nauczyciela oraz co oznacza troska i etyka troski w zawodzie nauczyciela. Jako metodę badawczą przyjęto analizę literatury przedmiotu zarówno zwartą, jak również artykułów zamieszczonych w czasopismach naukowych, dotyczącą podejmowanej problematyki badawczej. W przedstawionym tekście kolejno zaprezentowano: wymiar etyczny pracy zawodowej nauczyciela z perspektywy normatywnej, w szczególności z punktu widzenia etyki powinności i etyki cnoty, a następnie kategorię troski oraz etykę troski wraz z odniesieniem jej do aktywności zawodowej nauczyciela. Przeprowadzona analiza literatury przedmiotu skłania do przekonania, że we współczesnych eksploracjach naukowych wpisujących się w myśl etyczno-pedeutologiczną należy położyć większy nacisk na etykę troski w zawodzie nauczyciela, a także ewentualną możliwość kontaminacji etyki troski i etyki sprawiedliwości. Wszystko to służyć może optymalnemu uprawianiu zawodu nauczyciela pod względem etycznym. Słowa kluczowe: etyka zawodu nauczyciela, troska, etyka troski, relacje, opiekun spolegliwy